Oncogene PLCE1 may be a diagnostic biomarker and prognostic biomarker by influencing cell cycle, proliferation, migration, and invasion ability in hepatocellular carcinoma cell lines. Issue 10 (9th February 2020) - Wang, Xiang‐Kun; Liao, Xi‐Wen; Yang, Cheng‐Kun; Liu, Zheng‐Qian; Han, Quan‐Fa; Zhou, Xin; Zhang, Lin‐Bo; Deng, Teng; Gong, Yi‐Zhen; Huang, Jian‐Lu; Huang, Rui; Han, Chuang‐Ye; et al.
Abstract: Hepatocellular carcinoma (HCC) is a lethal malignancy worldwide. HCC has traits of late diagnosis and high recurrence. This study explored potential diagnosis and prognosis significance of phospholipase C epsilon 1 ( PLCE1 ) in HCC. The messenger RNA (mRNA) levels and diagnostic value of PLCE1 were determined by real‐time polymerase chain reaction and online databases GEPIA, oncomine, and GSE14520 data set. Survival analysis used the Kaplan–Meier Plotter website. Cell cycle, proliferation, migration, and invasion assays were performed with downregulated PLCE1 expression in HCC‐M and HepG2 cell lines. PLCE1 was differentially expressed and highly expressed in tumors and had low expression in nontumor tissues (all p < .05). The diagnostic value of PLCE1 was validated with the datasets (all p < .01, all areas under curves > 0.7). PLCE1 mRNA expression was associated with the overall and relapse‐free survival (both p < .05). Functional experiments indicated that downregulation of PLCE1 expression led to increased G1 stage in cell cycle and decreased cell proliferation, migration, and invasion compared with a negative control group (all p ≤ .05). The oncogene PLCE1 was differentially expressed in HCC and non‐HCC tissues. It is a candidate for diagnosis and serves as prognosis biomarker. PLCE1 influenced survival by affecting the cell cycle, proliferation, migration, and invasion ability. Abstract : We found that PLCE1 served as an oncogene and differentially expressed in HCC and non‐HCC tissues. It is a candidate for diagnosis and serves as prognosis biomarker. PLCE1 influenced survival by affecting the cell cycle, proliferation, migration, and invasion ability.